Effects of systematic exposure to foreign accented speech on speech intelligibility perceived by Libyan EFL learners - Salheen, Dalal Alfadhil Attaher (2020)
With the ever-increasing population of non-native speakers (NNSs) of English around the globe to the extent of exceeding the population of native speakers, encountering foreign-accented speech (FAS) has become frequent and inevitable. Numerous studies have indicated that FAS presents challenges for accurate and efficient speech communication due to reduction in speech intelligibility. However, empirical studies have shown that perceptual accuracy of accented speech can be improved by adequate exposure such as perceptual training. A body of research on auditory perception has demonstrated generalization of adaptation to FAS within shared-language background groups and also within different language background groups; however, many of these studies utilized native speakers of English as evaluators of the degree of intelligibility. Little attention has been paid to speech intelligibility among diverse groups of non- native speakers of English. Therefore, this study attempts to determine the degree of intelligibility of FAS to a group of non-native speakers of English using native and non-native speaker models as effecting variables to non-native speakers of English. It also seeks to assess the perceptual learning and benefits of systematic exposure to FAS through training. A training phase of 10 training sessions was conducted involving exposure to a variety of “sentence-level” accented English produced by a number of speakers from Malaysia, and native speakers of English from the U.S.A. The naïve Libyan EFL learners who were randomly selected served as listeners; they were divided into three groups according to the type of exposure. A single foreign accent (SFA) group listened to only Malay speakers of English; a multi-foreign accent (MFA) group listened to Malaysian speakers of English; i.e., Malays and Malaysians of Indian and Chinese descents and a no foreign-accent (NFA) group served as a control group whose listeners were exposed to speech from native English speakers. The Bench- Kowal-Bamford (BKB) standard sentences lists were used as the stimuli for the transcription tasks (tests and training materials). Speech samples were recorded in a quiet room using PRAAT (Boersma & Weenick, 2016; version 6.0.19), and presented to listeners in a phonetics laboratory. Data collection was conducted in three stages: (1) Pretest, which was given before training (2) Post-test A and (3) Post-test B. Both post-tests were administrated immediately after the 10 training sessions. Using SPSS (Version 22) and Microsoft Excel (2013), the data was descriptively and inferentially analysed. On average, the results revealed that the majority of Libyan EFL learners found difficulty in perceiving the Malaysian English variety. However, the results revealed that perceptual training was significantly efficient in improving intelligibility of FAS. Among the three types of training/ exposure, training with multiple foreign accents was the method with the most significant effectiveness to facilitate perception or to enhance intelligibility when exposed to unfamiliar FAS. Overall, the study concluded that a brief exposure to multiple accented speakers descending from different language backgrounds was sufficient to facilitate perception as it implies improvement in speech intelligibility, and it also attenuates initial perceptual difficulty when exposed to other unfamiliar foreign accented speech.